2022
DOI: 10.1177/09544089221081624
|View full text |Cite
|
Sign up to set email alerts
|

Process Modelling and Optimization using ANN and RSM during WSEM of Ni51.59Ti48.41 shape memory alloy

Abstract: Shape memory Ti-Ni alloys have fascinated significantly in recent years since these types of material are intelligent, shape memory and functional materials. These materials find many applications in the engineering and medical fields. In the current study, ‘Ni-Ti’ shape memory alloy (SMA) has been processed by wire spark erosion machining (WSEM). This research article explores the effects of controllable machining variables such as spark on-time, spark off-time, wire feed and servo voltage on productivity, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Step 2: The EF, SR, and MRR models are developed regarding process parameters by means of the ANN. 22,23 The ANN approach is named as an advanced processing and modeling technique for the obtained data, in which the biological behaviors of the human brain are simulated and reproduced. The ANN requires a number of layers and neurons, which are connected to produce the neural network.…”
Section: Optimization Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 2: The EF, SR, and MRR models are developed regarding process parameters by means of the ANN. 22,23 The ANN approach is named as an advanced processing and modeling technique for the obtained data, in which the biological behaviors of the human brain are simulated and reproduced. The ANN requires a number of layers and neurons, which are connected to produce the neural network.…”
Section: Optimization Approachmentioning
confidence: 99%
“…Step 2: The EF , SR , and MRR models are developed regarding process parameters by means of the ANN. 22,23…”
Section: Optimization Approachmentioning
confidence: 99%
“…Raju et al 27 experiments combined the Taguchi technique with a genetic algorithm to predict the WEDM's machining parameters and found that wire feed is the most significant influencing factor on material removal rate and surface roughness. Singh et al 28 used mathematics, ANOVA modeling, 29 tests carried out using the RSM technique, and artificial neural networks to predict the machining parameters. In a similar vein, Rajput et al 29 devised a combination of RSM and a genetic algorithm to evaluate the surface roughness in the hybrid-chemical magnetorheological finishing process.…”
Section: Introductionmentioning
confidence: 99%